Sound range-dependent propagation : An experiment on down-slope propagation over the Argentinian continental slope - Etcheverry de Milou, Marta I. (1994)
A range dependent acoustic down-slope propagation loss (TL) experiment was conducted in 1989 over the Argentinian Continental Slope, along a 50 km track, using two TRACKER aircrafts from the AntiSubmarine Warfare (ASW) squadron. One aircraft flew a prearranged track dropping 1.8 lb of TROTYL, explosive charges, while the second aircraft remained in the area of a deployed calibrated passive sonobuoy, used as sonar receiver. Recorded broadband signals were analyzed with EFT techniques in selected 1/3 octave bands between 100 Ilz and 400 Hz. A code based on the parabolic equation method (PE) was used to model the down-slope propagation losses. A reasonable agreement was obtained when theoretical predictions were compared with experimental evidence. This agreement improves at low frequencies. Moreover, at high frequencies the greater the range the better fit is observed.